Perancangan Interior Pusat Informasi dan Perawatan Hipnoterapi Bagi Ibu dan Anak di Surabaya - Felyshia Aditya Kurniawan; Stephanus P Honggowidjaja (Intra, 2015)
The Maternal Mortality Rate (MMR) in Indonesia is very high, compared to other countries because of the lack of knowledge and counseling about pregnancy in the community and low standard health care. In addition to the high MMR, children mortality in Indonesia is also high because of poor nutrition. The planning of Information and Hypnotherapy Care Center For Mother and Child in Surabaya will support government programs in reducing maternal and children mortality in Indonesia and also the development of early child's brain using hypnosis method (via media subconscious) which is good for the mother's and children's health. The supporting facilities provided are a small library and information center that provide information about the education of pregnancy, children's health, nutrition, pre-birth and post-birth education classrooms, ultrasound and consultation room, pregnancy gyms and yoga, spa for pregnant mother, baby's store, day care, and children treatment, with other supporting public facilities such as lobby, cafe, lounge area, office, toilet, warehouse, and employees' break room. Information and Hypnotherapy Care Center for Mother and Child will be the first place in Indonesia that provides all the supporting facilities for pregnancy, postpartum, and early children's brain development.